What are the effects of even-aged and uneven-aged forest management on boreal forest biodiversity in Fennoscandia and European Russia? : A systematic review protocol - Savilaakso, Sini; Häkkilä, Matti; Johansson, Anna; Uusitalo, Anne; Sandgren, Terhi; Mönkkönen, Mikko; Puttonen, Pasi (BioMed Central, 2019)
Abstract Background Biodiversity is vital for human well-being, but is threatened by human actions world-wide. In the boreal zone, harvesting and management of forests on an industrial scale is the most important factor driving habitat change and degradation. Over time different forest management regimes have been implemented but their impact on biodiversity at different spatial and temporal scales has not been systematically reviewed although non-systematic reviews on the topic exist. The aim of this article is to describe a protocol for a systematic review to synthesise and compare the impacts of two different forest management systems on biodiversity at different spatial and temporal scales. The topic for the systematic review arose from the discussions with the Finnish forestry sector and was further defined in a stakeholder workshop. Research questions addressed by the systematic review protocol are: (1) What are the stand-level effects of even-aged and uneven-aged forest management on boreal forest biodiversity in Fennoscandia and European Russia? (2) What is the effect of these same forest management systems on biodiversity at landscape level? Methods Animal, plant, and fungal diversity is addressed. Bibliographic databases and organizational websites will be searched, and internet search engines will be utilized to find relevant literature. The searches will be conducted in English, Finnish, Swedish, and Russian. Articles will be screened regarding the inclusion and exclusion criteria at title, abstract, and full-text stage. The validity of included studies will be evaluated against appraisal criteria and studies categorized based on their risk of bias. A narrative synthesis will be conducted to describe the findings. If enough quantitative data can be retrieved from the studies, a meta-analysis will be conducted.